Light Acclimation of the Colonial Green Alga Botryococcus braunii Strain Showa. Issue 3 (16th January 2019) - van den Berg, Tomas E.; Chukhutsina, Volha U.; van Amerongen, Herbert; Croce, Roberta; van Oort, Bart
Abstract : The colonial alga Botryococcus braunii acclimates to high light intensity by increasing the colony size and the extracellular accumulation of the sunscreen echinenone. Abstract: In contrast to single cellular species, detailed information is lacking on the processes of photosynthetic acclimation for colonial algae, although these algae are important for biofuel production, ecosystem biodiversity, and wastewater treatment. To investigate differences between single cellular and colonial species, we studied the regulation of photosynthesis and photoprotection during photoacclimation for the colonial green alga Botryococcus braunii and made a comparison with the properties of the single cellular species Chlamydomonas reinhardtii . We show that B. braunii shares some high-light (HL) photoacclimation strategies with C. reinhardtii and other frequently studied green algae: decreased chlorophyll content, increased free carotenoid content, and increased nonphotochemical quenching (NPQ). Additionally, B. braunii has unique HL photoacclimation strategies, related to its colonial form: strong internal shading by an increase of the colony size and the accumulation of extracellular echinenone (a ketocarotenoid). HL colonies are larger and more spatially heterogenous than low-light colonies. Compared with surface cells, cells deeper inside the colony have increased pigmentation and larger photosystem II antenna size. The core of the largest of the HL colonies does not contain living cells. In contrast with C. reinhardtii, but similar to other biofilm-forming algae, NPQ capacity is substantial in low light. In HL, NPQ amplitude increases, but kinetics are unchanged. We discuss possible causes of the different acclimation responses of C. reinhardtii and B. braunii . Knowledge of the specific photoacclimation processes for this colonial green alga further extends the view of the diversity of photoacclimation strategies in photosynthetic organisms.